NCOG-53. PREDICTORS OF ENDOCRINE OUTCOME AFTER ENDOSCOPIC TRANSSPHENOIDAL SURGERY FOR NON-FUNCTIONING PITUITARY ADENOMAS. (9th November 2020) - Hwang, Jenie; Yum, Diane; Chicoine, Michael; Dacey, Ralph; Osbun, Joshua; Rich, Keith; Zipfel, Gregory; Klatt-Cromwell, Cristine; Mcjunkin, Jonathan; Pipkorn, Patrik; Schneider, John; Silverstein, Julie; et al.
Abstract: BACKGROUND: Although endoscopic transsphenoidal surgery (ETSS) is an established treatment for patients with nonfunctioning pituitary adenomas (NFPAs), data are limited regarding the rates and predictors of pituitary dysfunction and recovery in a large cohort of NFPA patients undergoing ETSS. OBJECTIVE: To analyze the comprehensive changes in hormonal function and identify factors that predict recovery or worsening of hormonal axes following ETSS for NFPA. METHODS: Among a cohort of 601 consecutive patients who underwent ETSS for NFPA between 2010 and 2018 at Washington University in Saint Louis, recovery or development of new hypopituitarism was retrospectively analyzed in 209 patients. RESULTS: Preoperative endocrine deficits were observed in 59.8% of patients (125/209), and the deficit rates were 76.8% for male gonadal axis (86/112), 42.5% for thyroid axis, 25.8% for growth hormone axis, and 15.8% for cortisol axis. Recovery of preoperative pituitary deficit was noted in all four axes, with highest recovery in the cortisol axis with a 1-year cumulative recovery rate of 44.3%. New-onset postoperative hypopituitarism occurred most frequently in the thyroid axis (24.3%, 27/111) and least frequently in the cortisol axis (9.7%, 16/165). Multivariate analyses revealed axis-specific predictors of postoperative recovery and de novo deficiency. Older age was a negative predictor for recovery of both male hypogonadism (P= 0.04) and adrenal insufficiency (P=0.046), and a larger tumor volume was a negative predictor for recovery of hypothyroidism (P=0.043). Although higher body mass index was generally associated with any new postoperative pituitary deficit (P=0.03), most predictors of new onset deficits also differed by hormone axis. CONCLUSIONS: Dynamic changes in pituitary hormonal levels were observed in a significant fraction of patients following ETSS in NFPA patients. The specific hormonal axis dictated postoperative endocrine vulnerability, recovery, and predictors of recovery or loss of endocrine function.